Morphometric Analysis for Evaluation of Environmental Change and Disaster Reduction of Flood - ichsanul akbar (Sriwijaya Journal of Environment, 2019)
One indicator of environmental change due to climate change and human activities is changes in river flow and dynamics that can be seen on the visible scale and watershed. This study used geomorphic data which was an important factor for understanding natural processes that occur in efforts to reduced and managed flood risk. Changed in river morphometry would affect the characteristics of river flow, especially in watersheds that have meanders. Analysis was carried out on the Ogan River flow in the Ulak Pandan area and around by comparing flow changes in 1990 and 2016 as well as the used of land at the research site. The morphometry changes were analyzed by changing the width of the river and sinuosity parameters to evaluate the type of change that occurred. The results showed that there was an increase in the width of the river and the sinuosity index value at the same time it appeared that river meanders 5, 6 and 7 represented changes with the highest increase, whereas for land used to changed there was an increase in plantation land and agricultural land. This, indirectly by making changed to land use changed, the destruction of the natural vegetation of the river system results in degradation of river flow, especially in the outer meander arc.